Attitudes of Mayors Towards Gambling: Evidence from the Czech Republic (Lex localis - Journal of Local Self-Government, 2019)
Gambling is generally considered to be a socially negative phenomenon. On the other hand it also has its supporters, as proved by recent research. Mayors are important administrators of local affairs as they represent municipal governments. Their attitudes towards gambling vary and this could influence both the spatial distribution of gambling and the money accrued from gambling. Hence, knowledge of their attitudes is essential in gaining an understanding of the potential for further developments in the gambling landscape. The Czech Republic is the example discussed in this paper. The gambling environment is highly developed here and is a suitable laboratory for research on the mayors' attitudes to gambling. The interviews with the mayors were conducted using an extensive questionnaire. Our results show that the structure of the mayors attitudes toward gambling differs significantly according to the specific type of municipality. The text is accompanied by authentic statements from the mayors, which reveal the reasons for their attitudes to gambling.